Personal branding project in a sport marketing class. (June 2021) - Oshiro, Kristi F.; Brison, Natasha; Bennett, Gregg
Abstract: The purpose of this practice paper is to describe an experiential learning opportunity that sport management educators could integrate into coursework to enhance their students' understanding of building a personal brand. This project best fits into a course focused on sport marketing and consists of four components: 1) Individual brand video, 2) Personal Brand Audit, 3) Personal Brand Audit, 4) Project Critical Assessment. The personal branding project has many benefits for students, which include understanding the importance of developing a strong personal brand and the opportunity to obtain feedback and assistance in the process of auditing their current personal brand. While this is especially vital for senior-level students as they prepare for entry into the job market and a sustained career in the sport industry, this strategy can also be adopted for entry-level and graduate-level courses.